Determinants of Bank Performance in Nigeria: Do They Behave Differently With Risk-adjusted Returns? - Sanni, Mubaraq; Salami, Abdulai Agbaje; Uthman, Ahmad Bukola (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
The failure of banks in Nigeria has hitherto become a recurring phenomenon. Worried by the syndrome, this paper examines the determinants of bank performance in Nigeria taking into cognizance the duality of financial measures of bank performance. From an analysis of 115 bank-year observations of a sample of 17 Nigerian deposit money banks and macroeconomic data for the period 2012-2018 using Arellano-Bover one-step system GMM estimation approach, differences in the explanatory potential of these factors between the models with risk-neutral and risk-adjusted measures of performance as dependent variables are empirically established. This suggests that there is a higher probability of investors, depositors and other stakeholders being indecisive when analyzing the performance of banks. However, relying on the assumptions of risk-return hypothesis and level of risk embedded in banks’ operations could warrant them opting for determinants of risk-adjusted returns in their decision making. This study is exceptional in the bank performance literature for its long list of measures and drivers of bank performance.